Trade policy in a sovereign Palestinian State: What are the options in a final settlement? - Johanes Agbahey; Khalid Siddig; Harald Grethe; Jonas Luckmann (The World Economy, 2022)
This paper quantifies the economy-wide effects of different trade policies on the Palestinian economy, using a detailed database and a general equilibrium model adjusted to the particularities of the Palestinian economy. The findings show that a liberal and non-discriminatory trade regime provides the highest benefits for the Palestinian economy, in terms of welfare effects, GDP growth and job creation. The choice of an exchange rate regime has a considerable influence on the effects of trade policy. Accordingly, a full control over trade and monetary policy instruments could improve the capacity of the Palestinian National Authority to address the prevailing high unemployment and sluggish economic growth.
Keywords: 330; applied General Equilibrium; exchange rates; Middle East; Palestine; tariff-rate-quotas; unemployment